A formação continuada e a ressignificação da práxis pedagógica: revisitando a experiência formativa de professores no interior de SC - Meneghini, Neura (2024)
Continuing teacher training has been the subject of studies by many researchers, given its relevance for teaching in the classroom. However, the provision of continuing education does not guarantee that it actually contributes to the teacher's performance, as it is generally decontextualized, ineffective and superficial. When carried out by private institutes and companies, it aims for profit and is not in line with the needs of the school, nor even with a critical and reflective vision necessary for teaching work. Thus, the general objective of this dissertation was to describe, analyze and theorize about which concept of continuing education can actually contribute to re-signifying the teacher's pedagogical practice, revisiting a training experience of the 6th Regional Education Coordination, in Concórdia, SC, at light of the theoretical contribution of pedagogical praxis. The research presented here has a qualitative and quantitative approach, using the following methodological procedures: bibliographic and documentary survey, as well as the application of an (online) questionnaire to teachers and trainers of the aforementioned coordination. The main guiding question of this research is: given the needs in teacher training, what factors imply continued training that promotes reflection and construction of and about pedagogical praxis? Initially, we sought to substantiate the concepts of continuing training that permeate education, as well as analyze the provisions of current legislation regarding this topic. The commodification of training was approached from the perspective of a critical view, given the amount of supply that is emptied in content, objectives and context. In this context, critical, reflective and problematizing continuing education is brought to the fore, as a pressing need for teaching work permeated with meaning and that can contribute to the redefinition of pedagogical practice. The training experience project was described and the data obtained from the questionnaires was compiled. Finally, the analysis took place in light of the theoretical framework of the training concepts that are present in the ongoing training carried out, systematizing the training principles for continued training that is capable of giving new meaning to pedagogical practice. The research showed that the experience analyzed here contributed to the reframing of the teachers' pedagogical practice in a partial way, making it necessary to take praxis as a method, deepen the records and memories so that the continuity of the collective and collaborative training process is possible.